CASE REPORT: FELINE GINGIVOSTOMATITIS WITH CONJUNCTIVITIS IN DOMESTIC CAT - Azzra Hafifa; Ida Ayu Dian Kusuma Dewi; Putu Ayu Sisyawati Putriningsih (Buletin Veteriner Udayana, 2026)
Feline gingivostomatitis syndrome (FGS) is a chronic inflammatory disease of the feline oral cavity that is multifactorial in nature and often accompanied by conjunctivitis as a complication. This condition can significantly reduce a cat’s quality of life. The purpose of this report is to describe a case of FGS with conjunctivitis as a complication in a domestic cat, including anamnesis, clinical examination, supporting diagnostics, treatment provided, and evaluation of the treatment response. The method used was clinical observation of a 3-year-old female cat presenting with anorexia, hypersalivation, oral mucosal inflammation, ocular discharge, and nasal discharge. Examinations included a complete physical examination, complete blood count (CBC), rapid tests for Feline calicivirus (FCV) and Feline herpesvirus (FHV-1), as well as cytological examination of swabs from ocular discharge and gingiva. The results showed severe stomatitis with gingival ulceration, conjunctivitis with mucopurulent discharge, mild nasal discharge, anemia, thrombocytopenia, and lymphocytosis. Rapid tests for FCV and FHV-1 were negative. Treatment included Amoxiclav®, Methylprednisolone, Kenalog in Orabase®, topical Gentamicin, vitamin B12, and oral cavity cleansing with physiological saline solution. Evaluation on day 6 revealed clinical improvement, including increased appetite, reduced oral mucosal inflammation, disappearance of ocular and nasal discharge, and resolution of conjunctivitis. The conclusion of this case is that a combination therapy approach consisting of causative, symptomatic, and supportive treatments was effective in managing FGS with conjunctivitis as a complication. Long-term monitoring and routine vaccination are recommended to prevent recurrence.